University Education for Business : a Study of Existing Needs and Practices - Bossard, James H. S.; Dewhurst, J. Frederic (Philadelphia, Pa. : University of Pennsylvania Press, 2017)
An exhaustive survey of the subject, from both the economic and academic points of view, with pertinent suggestions for a closer harmony between collegiate training and the modern business world.
Frontmatter -- Foreword -- Preface -- Contents -- Part I. Modern Business and its Significance for Higher Education -- Chapter I. The Changing Character of American Business -- Chapter II. Occupational Opportunities for College Graduates in Business -- Chapter III. Training and Qualifications for Positions in Business -- Chapter IV. Reading Interests of Business Men -- Part II. Study of a Group of Business School Graduates -- Chapter V. Occupational Preferences and Undergraduate Training -- Chapter VI. Undergraduate Employment and Campus Activities -- Chapter VII. Occupational Experience of Graduates -- Chapter VIII. Opinions of Graduates as to College Training -- Part III. The Evolution of Higher Education for Business -- Chapter IX. The Development of Collegiate Education for Business -- Chapter X. Collegiate Schools of Business: Their Organization and Objectives -- Part IV. The Curricula of the Collegiate Schools of Business -- Chapter XI. The Organization of the Business Curricula -- Chapter XII. Certain General Studies -- Chapter XIII. The Business Studies -- Chapter XIV. Reported Trends in the Changing Business Curricula -- Part V. Problems of Personnel and Teaching Methods -- Chapter XV. Teaching Methods and Problems -- Chapter XVI. Problem of Faculty and Student Personnel -- Chapter XVII. Conclusions -- Index of Names
In English.
Online resource; title from PDF title page (publisher's Web site, viewed Jan. 23, 2017).
JSTOR
Keywords: Business education -- United States; Universities and colleges -- United States; Enseignement commercial -- États-Unis.; Universités -- États-Unis.; BUSINESS & ECONOMICS -- Education; Business education; Universities and colleges; United States